There are alternatives. Models for sustainable employment structures in the German system of higher education - Kuhnt, Mathias; Müßig, Peter; Reitz, Tilman (Frontiers in Research Metrics and Analytics, 2024)
The German system of higher education and public research is characterized by a high rate of temporary contracts with short contract durations and a nearly complete absence of structured career options. About 82% of employees not holding a full professorship have fixed-term contracts, with an average contract period of 20 months. This is facilitated by a special fixed-term employment law (Wissenschaftszeitvertragsgesetz) which universities and other public research institutions have stretched to its limits. Against the background of a survey which we conducted in 2021 and whose results once more demonstrate the shortcomings of this system, we discuss alternative options in the form of model calculations. We propose a reform of employment structures and career paths that could improve not only personal working conditions but also ensure the quality of research and teaching in German academia. By quantitative comparison with the current employment situation, our model calculation demonstrates that plannable career decisions can be enabled at an early stage without changing budgets or teaching duties. We also show that the counter argument of a “congestion” of positions is not substantiated, and that young scholars will still have the opportunity to start a career in the reformed system, while the total number of employees can be kept nearly constant.